Por um sindicalismo associativo: da solidariedade sindical internacional à democracia nos locais de trabalho - Kaufmann, Marcus de Oliveira (2012)
Four themes emerge from the study that is presented in favor of the idea of a associational unionism: the action, on the global ground, of multinational companies; the response of international trade unionism, by its most eloquent actors, towards capital; the ways in which workers can, from the workplace, organize themselves to participate in the governance of the company; and the interrelationship that labour, from the workplace to the international scene, may need to keep to their survival, in an complex environment of collective labour relations, with other types of collective representations of workers, from a non-union nature, assembled by singular means (personnel delegates or elected representatives of workers) or by collective means (committees or commissions of company or factory). The debate about the connections between supposed distant themes provide the material source from which the unions can expect to face the advance of capital, while they can build, from the workplace to the global field, democratic environments for more respectful and equal coexistence between labour and capital. One of the instruments, the study presents, for the union movement, particularly in Brazil, is the idea of a associational unionism, whereby unions, in a vertical orientation, link themselves, with information and experience traffic, by holding minimum rights regarding employee participation in the governance of the company, with various levels through which workers organize from the workplace to the international stage; and, in a horizontal orientation, link themselves, with information and experience traffic through the exploitation of rights of participation in the governance of the company, with collective representations of workers of a non-union nature, from the workplace to the international scene. So far the approach of all those interrelationships is not usual for the industrial relations Law in Brazil, although present though sometimes not so quiet or in a simple manner for the union movement in European countries and to countries seen as the "North", part of the bibliographic references eminently come from European and American perspectives, but not at any time losing the horizon of the political and legal Brazilian scene, as to propose, even in the context of the restrictive Brazilian union model, or beyond that model, new ways for the unionism act and think